2007
DOI: 10.1063/1.2800306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tensile and compressive strains on the transport properties of SmNiO3 layers epitaxially grown on (001) SrTiO3 and LaAlO3 substrates

Abstract: This paper deals with the role of epitaxial strain on the structure and electronic transport properties of metastable SmNiO3 layers grown by metal-organic chemical vapor deposition onto SrTiO3 and LaAlO3 substrates. The characterization of these layers is carried out by high resolution x-ray diffraction and four-probe resistivity measurements. It is found that the SmNiO3 phase is stabilized by in-plane compressive strain whereas in-plane tensile strain induces the creation of oxygen vacancies that induces an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 18 publications
(6 reference statements)
1
56
1
Order By: Relevance
“…Previously, the resistance modulation of bulk nickelates was achieved by adjusting the degree of oxygen deficiency during synthesis [31][32][33] . Recently, suppression or enhancement of the metallic phase of the nickelates was realized by introducing either tensile or compressive strain, which is believed to be able to regulate the Ni 3 þ /Ni 2 þ ratio [34][35][36] . The resistance modification from both methods is permanent and irreversible.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, the resistance modulation of bulk nickelates was achieved by adjusting the degree of oxygen deficiency during synthesis [31][32][33] . Recently, suppression or enhancement of the metallic phase of the nickelates was realized by introducing either tensile or compressive strain, which is believed to be able to regulate the Ni 3 þ /Ni 2 þ ratio [34][35][36] . The resistance modification from both methods is permanent and irreversible.…”
Section: Resultsmentioning
confidence: 99%
“…Epitaxial growth of pure NdNiO 3 films on a variety of substrates has shown a renormalization of T MI with respect to the bulk, that is, T MI is increased (decreased) by tensile (compressive) in-plane strain, an effect which is attributed to an increase (decrease) of the Ni-O-Ni, bond angle which affects films in the same way as the bulk. [9][10][11][12][13][14] Alternatively, it has been suggested that tensile in-plane stress may lead to a novel breathing distortion that creates two inequivalent Ni sites; charge transfer between these sites increases T MI.…”
mentioning
confidence: 99%
“…In this work, we study such alloyed films grown in registry with LaAlO 3 (001) substrates (pseudocubic indexing is used throughout), providing low-defect films with a homogeneous compressive strain; in addition, we use sample preparation aimed to avoid oxygen vacancies. 9 We characterize the transport, structural, and electronic properties of the films using resistivity measurements, synchrotron diffraction crystal truncation rod data, and x-ray absorption spectroscopy. From this, we produce an electronic phase diagram for thin films resembling that of the bulk, but with lower transition temperatures (renormalization) due to the effect of epitaxial strain.…”
mentioning
confidence: 99%
“…From the released literatures, it was found that the transport behavior of RNiO 3 films varied strongly as a function of preparation conditions, 15,16 substrate, [17][18][19][20][21] and film thickness 22, 23 as well. Especially, by virtue of epitaxial strain the MIT could be actively tuned in the films, while both suppressed 11,20 and enhanced 5 T MI induced by tensile strain have been reported.…”
Section: Introductionmentioning
confidence: 98%